Income inequality in rural China: Regression-based decomposition using household data - Guanghua Wan; Zhangyue Zhou (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
A considerable literature exists on the measurement of income inequality in China and its increasing trend. Much less is known, however, about the driving forces of this trend and their quantitative contributions. Conventional decompositions, by factor components or by population subgroups, only provide limited information on the determinants of income inequality. This paper represents an early attempt to apply the regression-based decomposition framework to the study of inequality accounting in rural China, using household level data. It is found that geography has been the dominant factor but is becoming less important in explaining total inequality. Capital input emerges as a most significant determinant of income inequality. Farming structure is more important than labour and other inputs in contributing to income inequality across households.
Keywords: D33; R12; O53; 330; inequality decomposition; regression; income generating function; China; Ländliche Einkommensverteilung; China